LEGAL STANDING KUASA ISTIMEWA UNTUK MEWAKILI MENGUCAPKAN IKRAR TALAK DALAM PERKARA CERAI TALAK - Muhammad Fajar Sidiq Widodo (MAHAKIM Journal of Islamic Family Law, 2019)
Talak is a marriage breaker pledge that is charged to a husband who wants to divorce his wife. Talak must be pronounced in a religious court. after permission by the Religious Court, a husband can declare his talak. However, what if a husband cannot pronounce his talak, then the best way is to represent it. The concept represents saying talak, both of which are equally permissible in Islamic law and in positive law. this paper will discuss how Legal Standing or the authority to act as a power of attorney to represent declaring talak. The purpose of this study is to explore and find concepts of special power that are not contrary to the Indonesian legal system. This research is normative research, because it examines the norms related to the granting and receiving the power of representation as part of a legal system. Then in this study using the Statute Approach and the Concept Approach to solve core problems.